Managing Dyspnea in Patients with Advanced Chronic Obstructive Pulmonary Disease: A Canadian Thoracic Society Clinical Practice Guideline - Darcy D Marciniuk; Donna Goodridge; Paul Hernandez; Graeme Rocker; Meyer Balter; Pat Bailey; Gordon Ford; Jean Bourbeau; Denis E O’Donnell; Francois Maltais; Richard A Mularski; Andrew J Cave; et al. (Canadian Respiratory Journal)
Dyspnea is a cardinal symptom of chronic obstructive pulmonary disease (COPD), and its severity and magnitude increases as the disease progresses, leading to significant disability and a negative effect on quality of life. Refractory dyspnea is a common and difficult symptom to treat in patients with advanced COPD. There are many questions concerning optimal management and, specifically, whether various therapies are effective in this setting. The present document was compiled to address these important clinical issues using an evidence-based systematic review process led by a representative interprofessional panel of experts.